Implementasi Business Intelligence Untuk Menganalisis dan Memvisualisasikan Data Penumpang Bus Transjakarta Menggunakan Tableau - Anwar Hidayat; Zuhri Halim; Firman Noor Hasan (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
The existence of transportation facilities such as the Transjakarta bus will make it easier for human activities to move from one place to another. This Transjakarta bus is used as an alternative choice of means of transportation by many people in Jakarta. Because Transjakarta buses use special lanes that allow faster travel. The purpose of this study is to analyze Transjakarta passenger data by implementing a Business Intelligence system to display the number of passengers by type of bus, the number of passengers by route, the most favorite type of bus, the total number of passengers, the average passenger and the top five bus routes. The research method used is dataset processing, namely data for Transjakarta bus passengers in 2021 sourced from data.jakarta.go.id and the data is processed using Tableau tools. The results of this research report are in the form of a dashboard, such as the number of passengers as many as 120,308,547 people and the average passenger is 81,676 people. It is hoped that reports made in the form of data visualization and dashboards can be used in decision making.